Optimised transformation model for contrast enhancement of satellite images using modified whale optimisation. (3rd April 2019) - Devika, G; Parthasarathy, Sudhaman
ABSTRACT: Image enhancement is possible only when sufficient information about the concerned is on hand. This would also directly reflect on the quality of the image. Enhancement of satellite image is deductively conceivable by processing a given image using soft computing technique. This paper introduces an endeavour to exhibit its versatility and adequacy for searching global optimal solutions for improving the contrast properties of a given image. The intensity of the image is enhanced by a parameterised transformation function, in which parameters are advanced by modified whale optimisation (MWO) as an objective function. The intensity transformation function utilises local and global information of the input image and the objective function considers the entropy and edge data to measure the image quality.